A Creative Teacher for Problematic Students: An Individual Psychological Study on Freedom Writers Movie - Nugroho, Abdillah (Universitas Muhammadiyah Surakarta, 2016)
The paper analyzed a creative teacher handling some variously problematic students in her classroom reflected in Freedom Writers movie. Based on the problem, the paper was aimed at analyzing ways that the creative teacher took to solve the students’ problems. The theoretical framework of the analysis was the Individual Psychological approach by Alfred Adler. Teacher has an important role in human life. As a teacher, he or she not only teaches but also educates the students. To teach means transforming the teacher’s knowledge to the students. Through interaction with students, a teacher gives them various materials of knowledge. The knowledge can be language, mathematics, biology, physics, history, and so on. Meanwhile, to educate means a teacher can educate the students about social norms, ethics, proper manner, morality and the like. To play their roles, teachers often face a lot of problems. The problems ranged from students’ personal problem, their environment problem, lack of facilities of teaching learning process, to their own private problem. Freedom Writers movie, in which the creation was inspired by a true story, delineates complex problems experienced by both the teacher and the students. The teacher, Erin Gruwell, faced her students who had various and complicated problems, which later motivated to find a solution for her students’ problem. Her students’ problem might be racial discrimination, social oppression by the dominant group, social injustice experienced by the marginalized group, and so on. With her creativity of teaching technique, Gruwell created some ways to understand their students’ private problem and found a wise way out of their problems.